Polymorphism of DNA mismatch repair genes in endometrial cancer - Poplawski, T.; Sobczuk, A.; Sarnik, J.; Pawlowska, E.; Blasiak, J. (Experimental Oncology, 2015)
Endometrial cancer (EC) is the second most common malignancy associated with hereditary non-polyposis colorectal cancer (HNPCC) family. The development of HNPCC is associated with defects in DNA mismatch repair (MMR) pathway resulting in microsatellite instability (MSI). MSI is present in a greater number of EC than can be accounted for by inherited MMR mutations, therefore alternative mechanisms may underline defective MMR in EC, including polymorphic variation. Aim: We checked the association between EC occurrence and two polymorphisms of MMR genes: a 1032G>A (rs4987188) transition in the hMSH2 gene resulting in a Gly22Asp substitution and a –93G>A (rs1800734) transition in the promoter of the hMLH1 gene. Material and methods: These polymorphisms were genotyped in DNA from peripheral blood lymphocytes of 100 EC patients and 100 age-matched women by restriction fragment length polymorphism PCR. Results: A positive association (OR 4.18; 95% CI 2.23–7.84) was found for the G/A genotype of the –93G>A polymorphism of the hMLH1 gene and EC occurrence. On the other hand, the A allele of this polymorphism was associated with decreased EC occurrence. The Gly/Gly genotype slightly increased the effect of the –93G>A-G/A genotype (OR 4.52; CI 2.41–8.49). Our results suggest that the –93G>A polymorphism of the hMLH1 gene singly and in combination with the Gly322Asp polymorphism of the hMSH2 gene may increase the risk of EC. Key Words: hMSH2, hMLH1, endometrial cancer, genetic polymorphism, MMR.